Recombinase Polymerase Amplification Combined with a Lateral Flow Strip for the Detection of Plasmodium knowlesi - Lai, Meng Yee; Ooi, Choo Huck; Lau, Yee Ling (American Society of Tropical Medicine and Hygiene, 2018)
The aim of this study was to develop a recombinase polymerase amplification (RPA) combined with a lateral flow (LF) strip method for specific diagnosis of Plasmodium knowlesi. With incubation at 37C, the 18S rRNA gene of P. knowlesi was successfully amplified within 12 minutes. By adding a specifically designed probe to the reaction solution, the amplified RPA product can be visualized on a LF strip. The RPA assay exhibited high sensitivity with limits of detection down to 10 parasites/μL of P. knowlesi. Nonetheless, it was demonstrated that all P. knowlesi (N = 41) and other Plasmodium sp. (N = 25) were positive while negative samples (N = 8) were negative. Therefore, a combination of RPA and LF strip detection is a highly promising approach with the potential to be suitable for use in resource-limited settings.